State Regulation of General Secondary Education in Ukraine: Historical Context - Khoruzha, Lyudmila; Bozhynskyi, Volodymyr (Educological discourse, 2025)
The article examines the historical context of state regulation of general secondary education in Ukraine on the basis of changes in legal and regulatory framework. State regulation as part of the national policy directly affects the development of the general secondary education system. The permanent reform of this system, which has been carried out since the end of the twentieth century, is primarily due to systematic changes in public policy. The combination of systematic and radical nature of such changes, their focus on building a democratic and pluralistic system is reflected and clearly seen in the transformational processes in the approaches and content of its legal regulation. The study reveals and correlates the essence of the concepts of “sphere of general secondary education” and “system of general secondary education”, “state regulation” and “regulatory and legal regulation”, and also considers the research of Ukrainian scholars who have studied the issues of reforming the system of general secondary education in the historical and pedagogical context and the problems of state regulation of this sphere of public life. The periods of regulatory and legal regulation of secondary education development in independent Ukraine (transitional and adaptation) are defined and examples of various documents and concepts of state regulation of this process are given. The tendencies of state regulation of general secondary education are characterized, based on the content of these legislative acts and the approaches used to develop them (evolutionary transition from the Soviet paradigm to the formation of a pluralistic model based on democratic principles; strengthening the place and role of local governments as a result of decentralization processes and the related need for regulation at the level of laws of Ukraine; increase in the number of legislative acts and conceptual documents (concepts), their increasing instability (variability) depending on political decisions; gradual stabilization of democratic approaches of public authorities to state regulation of general secondary education; increased involvement of civil society representatives in the development of legislative acts and conceptual documents (concepts), as well as the influence of public opinion on the final result of the activities of public authorities).